Strength training for cross-country skiers - Losnegard, T. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
This chapter provides an updated synopsis of the importance of strength abilities for performance in high-level cross-country skiers, with a focus on the upper body. It also provides an overview of the effect of training models in enhancing upper-body power, with a special emphasis on heavy strength training. In addition, the effect of alternative models on performance such as sport-specific speed training and muscular endurance training is discussed. Finally, a practical application of efficient strength training is provided, based on the distinctiveness of movement patterns in skiing techniques, and thus, the specificity of training for cross-country skiers. Abstract from author